Monte Carlo Investigation of Gamma Radiation Shielding Features for Bi2O3/Epoxy Composites - Karem G. Mahmoud; M. I. Sayyed; Aljawhara H. Almuqrin; Jack Arayro; Yasser Maghrbi (Applied Sciences, 2023)
Three different samples were synthesized based on polyepoxide resin, a solidifying agent, and a Bi2O3 doping compound. The polyepoxide resin and solidifying agent were added in a 2:1 ratio by weight and the Bi2O3 compound was added in ratios of 0, 5, and 10 wt. %. The density of the synthesized composites was measured using an MH-300A densimeter with an uncertainty in measurement of 0.001 g/cm3. The measurements showed that the density of the fabricated composite varied from 1.103 g/cm3 to 1.20 g/cm3 when the reinforcing Bi2O3 compound was raised from 0 wt. % to 10 wt. %. Furthermore, the γ-ray shielding parameters were evaluated based on the simulated mean track length of γ-photons inside the synthesized composites using MCNP-5 code. The simulated results show an enhancement in the shielding parameter when increasing the Bi2O3 concentration, where the linear attenuation coefficient values increased from 0.101 cm−1 to 0.118 cm−1 as the Bi2O3 concentration increased from 0 to 10 wt. %. The increase in the LAC has a positive effect on the other shielding properties.